Competing internationally: On the importance of R&D for export activity - Dirk Czarnitzki; Annelies Wastyn (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Export is an important factor to improve growth and welfare especially for industrialized small, open economies such as Belgium. Policy may be interested in key variables that can influence export. This paper finds evidence for the importance of R&D for export activities using Belgian firm-level data. To control for reverse causality, R&D-subsidy variables are used to instrument R&D. The results show that R&D policies may indirectly help to increase the export performance of the economy. Due to the exceptionally high openness of Belgium, two subsamples of firms are considered, domestic firms and multinational firms. We observe positive effects of R&D on export for both domestic and MNEs. Once we instrument R&D because of its potential endogeneity, however, it turns out that the effect of R&D on exports is larger for domestic firms than for multinational companies.
Keywords: F23; O33; O38; 330; Export; R&D; Multinational enterprises; Innovation Policy; Industrielle Forschung; Innovation; Exportindustrie; Multinationales Unternehmen; Forschungssubvention; Wirkungsanalyse; Belgien